2011
DOI: 10.1193/1.3651624
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Behavior of Framed Masonry Panels with Prior Damage When Subjected to Out-of-Plane Loading

Abstract: Framed masonry panels are subjected to both in-plane and out-of-plane loading during earthquakes and their load-carrying capacity in the out-of-plane direction after being damaged is crucial for overall stability and safety. To assess the effect of in-plane damage on their out-of-plane behavior, three half-scaled clay brick framed masonry panels were subjected to a sequence of slow cyclic in-plane drifts and shake table-generated out-of-plane ground motions. The framed panels maintained structural integrity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 8 publications
0
30
0
Order By: Relevance
“…The testing method involved successive applications of out-of-plane and in-plane loading [11]. The test setup for the out-of-plane and in-plane loading are shown in Figure 3.…”
Section: Test Procedures and Loading Historymentioning
confidence: 99%
See 1 more Smart Citation
“…The testing method involved successive applications of out-of-plane and in-plane loading [11]. The test setup for the out-of-plane and in-plane loading are shown in Figure 3.…”
Section: Test Procedures and Loading Historymentioning
confidence: 99%
“…Earlier experimental studies on masonry infill frames concluded that the prior in-plane damage could significantly reduce the out-of-plane capacity of infill panels [9][10][11]. Earlier experimental studies on masonry infill frames concluded that the prior in-plane damage could significantly reduce the out-of-plane capacity of infill panels [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…From the available published experimental [134,31,189,70,87,[92][93][94]138,139,17,158,103,140,95,100,175,132,71] and numerical [135,128,80,86,11,16,186,67,164,64,69,60,161] [110,17,18,42,37,68,172,76,144,176,24,96] data, it can be observed that masonry infill walls (referred to also as infill walls in this paper) can have a significant effect on the structural performance of RC frames under seismic actions. This can result in a localized or global increase of strength and stiffness depending on the extent and the position of the infill walls within the frame.…”
Section: Introductionmentioning
confidence: 94%
“…Models based on the arching behaviour provide conservative or unconservative estimates of the capacity according to the model under consideration. Moreover, there are situations in which the arching behaviour does not develop even in the case of small slenderness [26,27].…”
Section: Discussionmentioning
confidence: 99%